The use of LMS by students in Malaysian universities - Alnjjar, Ayish S.M (Kulliyyah of Economics and Management Science, International Islamic University Malaysia, 2019)
In view of the increased adoption of technology by higher learning institutions around the world, this study aims to examine the extent to which Learning Management Systems (LMS) are being used by students in Malaysian universities. The study proposes a modified version of the Technology Acceptance Model (TAM). Specifically, the study investigates how students' self-efficacy impacts their perceptions of the LMS' usefulness and ease of use and how those perceptions influence students attitude to actually use the LMS of their universities. The quantitative research method was employed to collect and analyse data. A total of 288 usable questionnaires were received from students in 17 public and private universities in the Klang Valley region. The Statistical Package for the Social Sciences (SPSS) was used to perform descriptive statistics and exploratory factor analysis, while the Analysis of Moment Structures (AMOS) software was used to perform structural equation modelling (SEM) which constitutes of confirmatory factor analysis and hypotheses in order to answer the research questions. The findings revealed that self-efficacy has a significant positive effect on perceived ease of use and perceived usefulness of the LMS. Students' attitude towards using the LMS of their universities was found to be significantly influenced by their perceptions of the usefulness and ease of using the system. It was also revealed that when students perceived a system to be easy to use their perception of its usefulness was high. Finally, students' attitude towards using universities' learning management systems significantly influenced the actual use of those systems. Overall, the study had several contributions to theoretical knowledge and how it is being practiced within higher learning institutions in Malaysia. Both students and universities may benefit from these findings in order to enhance the experience of using LMS which in turn is expected to positively impact the performance on various levels, and this can be an objective for future studies. However, despite these contributions, there have been some limitations related to the lack of updated official statistics about the number of students and the nature of using LMS in Malaysian universities, in addition to some difficulties during the data collection process.